2007
DOI: 10.1021/ic061868e
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Binding of a l-Cysteinato Cobalt(III) Octahedron to a Cadmium(II) Center

Abstract: The binding ability of a chiral L-cysteinato cobalt(III) complex, [Co(L-cys-N,S)(en)2]+ (l-H2cys = L-cysteine, en = ethylenediamine), toward a cadmium(II) center, together with the construction of S-bridged CoIIICdII structures that are controlled by anions and pH, is reported. The reaction of Lambda(L)-[Co(L-Hcys-N,S)(en)2](ClO4)2 having a pendent COOH group with CdCl2 in a 1:1 ratio in water, followed by the addition of NaCl, gave an S-bridged CoIIICdII dinuclear complex, Lambda(L)-[CdCl4{Co(L-Hcys-N,S)(en)2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…The Cd-O bond lengths (2.228(3) to 2.357(3) A ˚) and the Cd-S bond length (2.6635(10) A ˚) are within the normal range. [62][63][64][65][66] The O-Cd-O and O-Cd-S angles range from 72.81(6) to 172.04 (10) (Table 1). The two carboxylato groups of Ts-cmc in this complex present different coordination modes.…”
Section: Molecular Structures Of Complexes 1-6mentioning
confidence: 99%
“…The Cd-O bond lengths (2.228(3) to 2.357(3) A ˚) and the Cd-S bond length (2.6635(10) A ˚) are within the normal range. [62][63][64][65][66] The O-Cd-O and O-Cd-S angles range from 72.81(6) to 172.04 (10) (Table 1). The two carboxylato groups of Ts-cmc in this complex present different coordination modes.…”
Section: Molecular Structures Of Complexes 1-6mentioning
confidence: 99%
“…The Cd-Cl bond distances are between 2.4677(6) Å and 2.4992(6) Å with a mean value of 2.4844(7) Å, which is comparable with data documented previously. [12][13][14][15] The dihedral angle of two anions, the charge of the Me 4 bim moiety should be +2, as in the cases found in the literature. [16][17][18][19][20] The Me 4 bim moieties are interconnected to the [CdCl 4 ] 2− anions via C-H•••Cl hydrogen bonds, yielding a supramolecule, as shown in Fig.…”
Section: Resultsmentioning
confidence: 77%
“…The Cd-Cl bond distances are between 2.4677(6) Å and 2.4992(6) Å with a mean value of 2.4844(7) Å, which is comparable with data documented previously. [12][13][14][15] The dihedral angle of two (7) Cl(2)-Cd(1)-Cl(4) 105.77(2) Cd(1)-Cl (2) 2.4677 (6) Cl (1) The solid-state emission spectra of 1 were measured at room temperature. The emission spectra of 1 are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The bond lengths of Cd-Cl are 2.4415(7) and 2.4813(7) Å with an average value of 2.4614(7) Å, comparable with those reported previously. [8][9][10][11] The bond angles of Cl-Cd-Cl are in the range 97.63(4)°-115.05(3)°, close to that for one regular tetrahedron. Bond valence calculation showed that the cadmium atom is in a +2 oxidation state (Cd1: 2.143).…”
Section: Resultsmentioning
confidence: 88%